Improving Quality in the Treatment of Pediatric Forearm Fractures: Minimizing the Need for Repeat Intervention With Long-arm Extension Casting. Issue 7 (August 2020) - Neal, Kevin M.; Osterbur, Todd A.; Kiebzak, Gary M.
Abstract : Purpose: Repeat intervention for pediatric forearm fractures after closed manipulation is as high as 46% with flexed elbow (FE) long-arm casts. Casting with the elbow extended (EE) has been advocated as an alternative technique. We documented outcomes of patients treated with closed manipulation and casting with EE long-arm casts for displaced, diaphyseal both-bone forearm fractures. Methods: We retrospectively reviewed charts for patients who had sedated manipulations and casting for closed, diaphyseal forearm fractures. Open fractures, immediate surgical intervention, metabolic bone disease, recurrent fractures, and Monteggia injuries were excluded. Closed manipulations were performed by orthopaedic residents assisted by cast technicians, with sedation provided by emergency department physicians. Radiographic angulation and displacement of the radius and ulna on immediate postreduction radiographs and all follow-up radiographs were recorded. Patients requiring repeat intervention were compared with those who did not by using the Mann-Whitney U and Fisher exact tests. Results: Of 86 patients (7.2±2.8 y) available for analysis, 82 (95.3%) completed treatment after a single-sedated manipulation and placement of an EE long-arm cast. There were no malunions or nonunions. The average follow-up was 50 days. Four (4.7%) patients required repeat interventions (2 had surgery, 1 had a repeat sedated manipulation, and 1 had a nonsedated manipulation). There were no statistically significant differences in age, sex, laterality, fracture position in the diaphysis, or immediate postreduction angulation of the radius or ulna. A literature review showed average repeat intervention rates of 14.9% (range, 0% to 45.9%) for FE casts and 3.3% (range, 0% to 15%) for EE casts. Conclusions: There was a low rate of repeat interventions (4.7%) in patients with EE casts compared with historical rates for FE casts. Improving the quality of health care involves identifying and implementing practices that provide the best outcomes at the lowest costs. The use of EE long-arm casts following closed manipulation of pediatric forearm fractures may decrease the rate of repeat manipulation or surgery compared with conventional FE casts. Level of Evidence: Level IV—case series.